Effect of geometrical parameters on the performance of conventional Savonius VAWT: A review - Cuevas-Carvajal, N.; Cortes Ramirez, J.S.; Norato, Julian A.; Hernández Acevedo, Camilo; Montoya Vallejo, Miguel Fernando (ElSevier, 2022)
Wind power is one of the main sources of renewable energy. New applications of this technology are currently under development through small vertical axis wind turbines, allowing energy production in small spaces even at low wind speeds. Therefore, creating an effective turbine design methodology tailored to these operating conditions has been the subject of extensive research. The Savonius-type vertical axis wind turbine is one of the most widely used due to its low cost and easy manufacturing. Several works have examined the effect of various geometric parameters on the performance of the Savonius-type wind turbine. However, there are no published overarching conclusions about these works. Thus, this paper aims to review and discuss in a concise way experiments and simulations carried out by several authors evaluating the effect of some geometric parameters on the maximum power and torque coefficient of Savonius vertical axis wind turbines. The paper also discusses additional experiments that should be performed in future work.

La energía eólica es una de las principales fuentes de energía renovable. Actualmente se están desarrollando nuevas aplicaciones de esta tecnología a través de pequeños aerogeneradores de eje vertical, que permiten la producción de energía en espacios reducidos incluso a bajas velocidades del viento. Por ello, la creación de una metodología de diseño de turbinas eficaz y adaptada a estas condiciones de funcionamiento ha sido objeto de una amplia investigación. El aerogenerador de eje vertical tipo Savonius es uno de los más utilizados debido a su bajo coste y su fácil fabricación. Varios trabajos han examinado el efecto de varios parámetros geométricos en el rendimiento del aerogenerador tipo Savonius. Sin embargo, no existen conclusiones generales publicadas sobre estos trabajos. Por ello, este artículo tiene como objetivo revisar y discutir de forma concisa los experimentos y simulaciones realizados por varios autores que evalúan el efecto de algunos parámetros geométricos en la potencia máxima y el coeficiente de par de los aerogeneradores de eje vertical Savonius. El artículo también analiza experimentos adicionales que deberían realizarse en trabajos futuros.
Keywords: Savonius-type wind turbine; Small vertical axis wind turbine; Renewable Energy; Geometric parameters